The Demonstration of Linguistic, Cognitive and Socio-cultural Dimensions of Academic Literacy in Nursing Students’ Written Texts - Nurakhir, Asih; Yuliasri, Issy; Linggar Bharati, Dwi Anggani (JPI (Jurnal Pendidikan Indonesia), 2020)
This study aimed to evaluate the demonstration of linguistic, cognitive, and socio-cultural dimensions of academic literacy in the written texts produced by the students of the nursing program. A descriptive qualitative research design was used to meet the purpose of the study. Data were collected from the students’ written texts, which served as the students’ responses to an English quiz. Fifteen out of fifty-two students’ written texts were randomly selected for the analysis. A modified scale table from the existing literature was used as a guideline during the analysis. This scale describes an assessment of the three dimensions of literacy: linguistic, cognitive, and socio-cultural. The results of the analysis showed that, in general, the students had a fair level of linguistic, cognitive, and socio-cultural dimensions of literacy. They could partially use layouts, punctuations, capitalizations, verb conjugations, and agreement as well as spelling. They also seemed to be familiar with some types of texts and generic structures, as well as linguistic features. However, there was evidence that students provided a less complete response and sometimes irrelevant information as well as an inconsistent interpretation of the subject of the text. This study indicates a high need for nursing students to improve their ability in academic literacy in English. As academic literacy is not a natural phenomenon, instead a learned ability, it should be developed and fostered in the educational institutions.